2014
DOI: 10.1002/eji.201444876
|View full text |Cite
|
Sign up to set email alerts
|

Human intestinal epithelial cells respond to β‐glucans via Dectin‐1 and Syk

Abstract: Intestinal epithelial cells (IECs

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
100
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(107 citation statements)
references
References 56 publications
4
100
0
1
Order By: Relevance
“…S4), consistent with previous studies demonstrating dectin-1 expression by human gut and airway epithelial cells (19, 20). Although nonepithelial structural cells (CD45 − EpCAM − ) in human nasal tissue also express dectin-1, such expression appears to be relatively minimal compared with epithelial cells (fig.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…S4), consistent with previous studies demonstrating dectin-1 expression by human gut and airway epithelial cells (19, 20). Although nonepithelial structural cells (CD45 − EpCAM − ) in human nasal tissue also express dectin-1, such expression appears to be relatively minimal compared with epithelial cells (fig.…”
Section: Resultssupporting
confidence: 91%
“…Although dectin-1 expression has been primarily associated with antigen-presenting cells (APCs), recent studies have demonstrated that dectin-1 is also expressed by mucosal epithelial cells (19, 20). Moreover, because epithelial cells are a primary source of IL-33 in the lungs (2125), we ascertained the contribution of Clec7a expression in hematopoietic and nonhematopoietic compartments to allergic airway disease.…”
Section: Resultsmentioning
confidence: 99%
“…It was also reported that laminarin activates human intestinal epithelial cells to secrete pro-inflammatory chemokines (IL8 and CCL2) (9). Furthermore, Drosophila gram-negative bacteria binding protein-1 (DGNBP-1) can bind to LPS and laminarin to enhance immune-related gene expression (11).…”
Section: Discussionmentioning
confidence: 99%
“…In both adult and larval locusts, the injection of laminarin has been shown to induce immune responses (7,8). It was reported that laminarin activates human intestinal epithelial cells to secrete proinflammatory chemokines such as interleukin-8 (IL8) and chemokine (C-C motif) ligand 2 (CCL2) in adectin-1 and spleen tyrosine kinase (SYK)-dependent manner (9).…”
mentioning
confidence: 99%
“…Expression of dectin-1 was originally thought to be primarily restricted to myeloid cells, including DCs, monocytes, macrophages, and neutrophils, although human B cells and subsets of T cells also express this receptor [1]. More recently, expression of dectin-1 has been described in human mast cells, keratinocytes, and epithelial cells [2-4]. …”
Section: Dectin-1mentioning
confidence: 99%